Utilising coverage holes and wireless relays for mobile target tracking. (3rd January 2011) - Ooi, Chia Ching; Schindelhauer, Christian
In this paper, wireless relays and sensing coverage holes are utilised to aid mobile target tracking in dense and sparse networks. First, we introduce Distributed Relay-robot Algorithm (DRA) that consists of target information dissemination by the relays and prediction of target position by the pursuer. Simulated results show that DRA performs efficiently in dense networks. To improve the strategy in sparse networks, we introduce Smart Ring that takes the advantages of sensing coverage holes. Sensors not only act as communication relays, but also take part in planning pursuer's path. Sensors forming the ring of a coverage hole gather and provide target information to the pursuer. Once a target is detected, sensor mobility or activity is coordinated such that the pursuer benefits from the variable size of the coverage hole. We perform simulation study to evaluate how feasible and efficient the proposed strategy is running in different modes.